2023
DOI: 10.1186/s13578-023-00987-8
|View full text |Cite
|
Sign up to set email alerts
|

RBX1 regulates PKM alternative splicing to facilitate anaplastic thyroid carcinoma metastasis and aerobic glycolysis by destroying the SMAR1/HDAC6 complex

Abstract: Background Anaplastic thyroid carcinoma (ATC) is one of the most aggressive malignancies, frequently accompanied by metastasis and aerobic glycolysis. Cancer cells adjust their metabolism by modulating the PKM alternative splicing and facilitating PKM2 isoform expression. Therefore, identifying factors and mechanisms that control PKM alternative splicing is significant for overcoming the current challenges in ATC treatment. Results In this study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…BANP (also known as SMAR1) is encoded by a gene located on chromosome 16q24.3 in humans and is expressed in heart, liver, spleen, lung, kidney, brain and thymus tissues, with the highest expression in the thymus 36 . The main role of BANP in tumours is to regulate the cell cycle, prevent tumour metastasis and invasion through the transforming growth factor (TGF-β) pathway, and regulate cytoskeletal dynamics and the NF-κB signalling pathway 37 . Studies have found that BANP could arrest the cell cycle at the G1/S and G2/M boundaries, and the mechanism might be p53 activation by BANP, but it has not been fully elucidated 38 .…”
Section: Discussionmentioning
confidence: 99%
“…BANP (also known as SMAR1) is encoded by a gene located on chromosome 16q24.3 in humans and is expressed in heart, liver, spleen, lung, kidney, brain and thymus tissues, with the highest expression in the thymus 36 . The main role of BANP in tumours is to regulate the cell cycle, prevent tumour metastasis and invasion through the transforming growth factor (TGF-β) pathway, and regulate cytoskeletal dynamics and the NF-κB signalling pathway 37 . Studies have found that BANP could arrest the cell cycle at the G1/S and G2/M boundaries, and the mechanism might be p53 activation by BANP, but it has not been fully elucidated 38 .…”
Section: Discussionmentioning
confidence: 99%
“…2.Promote MTC apoptosis and enhance cancer cell sensitivity to ionizing radiation [ 59 , 62 , 65 , 68 , 69 , 139 , 140 ] MDM4 PTC, ATC p53 1.Downregulate with tumor progression in PTC and associate with PTC non-multifocality 2. Increase survival of mice with wild-type p53 when reduced in ATC [ [63] , [64] , [65] ] Praja2 PTC, ATC PKA cAMP/Praja2/PKA 1.Overexpressed in PTC, Activate cAMP signaling pathway, promote proliferation 2.Low expression in ATC, can be used to monitor the degree of tumor malignancy [ 124 ] Rbx1 PTC, ATC SMAR1, NRF2 Rbx1/SMAR1/PKM1 promote invasion, migration, promote carcinogenic potential, inhibit autophagy [ 130 , 152 ] RNF150 PTC ASK1 RNF150/ASK1/p38 Downregulated in PTC, inhibit MAPK signaling pathway, inhibit proliferation, migration [ 129 ] SH3RF3 PTC miR-192-5p/SH3RF3 Promote invasion, migration [ 118 ] SKP2 PTC, FTC, ATC p27, PHLPP1 1.SKP2/PHLPP1/AKT 2. SKP2/p27 Promote proliferation, inhibit apoptosis and autophagy [ 55 , 97 , 114 ] …”
Section: Discussionmentioning
confidence: 99%
“…As an E3 ligase, RBX1 ubiquitinates scaffold/matrix attachment region binding protein 1 (SMAR1), down-regulating its expression. The SMAR1/histone deacetylase 6 (HDAC6) complex, involved in pyruvate kinase M1/2 (PKM) alternative splicing, is down-regulated as a result, down-regulating PKM1 and up-regulating PKM2, ultimately promoting ATC development by enhancing the Warburg effect [ 152 ].…”
Section: Anaplastic Thyroid Cancermentioning
confidence: 99%